Ab initio investigations in amorphous silicon dioxide: Proposing a multi-state defect model for electron and hole capture. (December 2022) - Wilhelmer, Christoph; Waldhoer, Dominic; Jech, Markus; El-Sayed, Al-Moatasem Bellah; Cvitkovich, Lukas; Waltl, Michael; Grasser, Tibor
Abstract: Experiments as well as theoretical calculations indicate that point defects in the amorphous SiO2 layer of electronic devices as well as in optical fibers are responsible for numerous stability and reliability phenomena, including noise, hysteresis, bias temperature instabilities and decreasing transmission efficiency. In addition to the well-known oxygen vacancy, hydrogen related defects such as the hydrogen bridge and the hydroxyl- E ′ center have gained a considerable amount of attention in the recent past, as they are suspected to negatively influence the device performance by capturing charge carriers from e.g. both Si and SiC substrates in field effect transistors. Here, we present a thorough ab initio study of these oxide defects and develop a unified description of electron and hole capture processes in a single multi-state model, supported by a comprehensive analysis of various defect parameters like relaxation energies, charge transition levels, (meta-)stability and transition barriers. We show that a single oxide defect can have two different trap levels for both electron and hole capturing processes, which might be the cause of anomalous device degradation phenomena. Based on its low formation energy compared to other defect types, we find that the hydroxyl- E ′ center is the most promising defect candidate to explain charge capture processes in Si/SiO2 systems. Furthermore, we argue that the reduced effect of positive bias temperature instability (PBTI) observed in MOS devices compared to its negative counterpart (NBTI) can be explained by the locations of the hydroxyl- E ′ centers charge transition levels. Highlights: Statistical ab initio investigations of hydrogen related defects in amorphous SiO2 . Electron and hole trapping processes and (meta-)stable states in a single nonradiative multi-phonon model. Investigations of negatively charged hydroxyl- E' center configurations. Formation energy, relaxation energy and charge transition barrier statistics. Charge transition level analysis for SiC/SiO2 and Si/SiO2 systems.